Perencanaan Investasi Jangka Pendek pada Penambangan Andesit PIT 3 PT. Mega Sejahtera Sugan Pangkalan Kab. Limapuluh Kota Sumatera Barat - Rugbia Natasya; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. To reach the companies' selling and production target with a balanced cost is a goal that must be done with a careful planning. This research was conducted due to the fact that PT. Mega Sejahtera Sugan often does not meet the production targets and there is no detailed cost in daily investing production activities.To find out the details of the investment that needs to be spent, as well as knowing the estimated revenue in mining production activities, it is necessary to analyze a short-term investment plan based on the monthly sequence of production. This research was conducted using quantitative methods, by doing calculations in solving problems in order to get the most effective solution. The solutions obtained for PT. Mega Sejahtera Sugan are to make improvements to employee working hours and add two new dumptrucks. With the addition of new units in production activities it is estimated that it can provide greater profits than the company's target. Production that has been done at PT. Mega Sejahtera Sugan are often does not meet the target, and there is a lot of waiting time for the excavator unit, thus resulting in the company's income achieved only 30% of the expected target, which is IDR 1,342,522,500.- from IDR 4,500,000.- per month. Meanwhile, if the dump truck unit is added, it will generate income of IDR 4,656,300,000.- per month, which will greatly benefits the company. Keywords: investment, quantitative, cost, income, production target